An ethnobotanical survey of indigenous medicinal plants in Hafizabad district, Punjab-Pakistan - Umair, Muhammad (PLoS One, 2017)
Present paper offers considerable information on traditional uses of medicinal plants by the inhabitants of Hafizabad district, Punjab-Pakistan. This is the first quantitative ethnobotanical study from the area comprising popularity level of medicinal plant species intendedby using relative popularity level (RPL) and rank order priority (ROP) indices.Ethnobotanical data were collected by interviewing 166 local informants and 35 traditional health practioners (THPs) from different localities of Hafizabad district. Demographic features of informants; life form, part used, methods of preparation, modes of application and ethnomedicinal uses were documented. Ethnobotanical data were analyzed using quantitative tools, i.e. Relative frequency citation (RFC), use value (UV), informant consensus factor (ICF) fidelity level (FL), RPL and ROP indices. A total of 85 species belonging to 71 genera and 34 families were documented along with ethnomedicinal uses. Solanum surattense, Withania somnifera, Cyperus rotundus, Solanum nigrum and Melia azedarach were the most utilized medicinal plant species with highest used value. The reported ailments were classified into 11 disease categories based on ICF values and highest number of plant species was reported to treat dermatological and gastrointestinal disorders. Withania somnifera and Ranunculus sceleratus with maximum FL (100%), were used against gastrointestinal and urinary disorders, respectively. The RPL and ROP values were calculated to recognize the folk medicinal plant wealth; six out of 32 plant species (19%) were found popular, based on citation by more than half of the maximum number of informant viz. 26. Consequently, the ROP value for these species was more than 75. The comparative assessment with reported literature revealed 15% resemblance and 6% variation to previous data;however79% uses of the reported species were recorded for the first time. The diversity of medicinal plant species and associated traditional knowledge is significant in primary health care system. Medicinal plant species with high RPL values should be screened for comprehensive phytochemical and pharmacological studies. This could be useful in novel drug discovery and to validate the ethomendicinal knowledge.